Inconsistency of Pancasila Cita (Law) for Natural Resources Management - Gatot Dwi Hendro Wibowo (Yayasan Rumah Peneleh, 2019)
This article aims to explain the legal study side of the existence of indications of inconsistency in the management of natural resources and the environment. The inconsistencies studied are between Pancasila as the ideal foundation and ground norm of the Indonesian nation as well as the ideals of the Indonesian nation's law, with the 1945 Constitution as a constitutional foundation as well as the rule of the game in the life of the nation and state, along with its organic laws. This article is a literature review. This article produces 3 arguments namely at the macro, micro, and socio-cultural level. On a macro scale, the spirit of